Quantitative analysis of ruminal bacterial populations involved in lipid metabolism in dairy cows fed different vegetable oils - Vargas-Bello-Perez, E.; Cancino-Padilla, N.; Romero, J.; Garnsworthy, P.C. (Cambridge University Press, 2016)
Vegetable oils are used to increase energy density of dairy cow diets, although they can provoke changes in rumen bacteria populations and have repercussions on the biohydrogenation process. The aim of this study was to evaluate the effect of two sources of dietary lipids: soybean oil (SO, an unsaturated source) and hydrogenated palm oil (HPO, a saturated source) on bacterial populations and the fatty acid profile of ruminal digesta. Three non-lactating Holstein cows fitted with ruminal cannulae were used in a 3x3 Latin square design with three periods consisting of 21 days. Dietary treatments consisted of a basal diet (Control, no fat supplement) and the basal diet supplemented with SO (2.7% of dry matter (DM)) or HPO (2.7% of DM). Ruminal digesta pH, NH3-N and volatile fatty acids were not affected by dietary treatments. Compared with control and HPO, total bacteria measured as copies of 16S ribosomal DNA/ml by quantitative PCR was decreased (P < 0.05) by SO. Fibrobacter succinogenes, Butyrivibrio proteoclasticus and Anaerovibrio lipolytica loads were not affected by dietary treatments. In contrast, compared with control, load of Prevotella bryantii was increased (P < 0.05) with HPO diet. Compared with control and SO, HPO decreased (P < 0.05) C18:2 cis n-6 in ruminal digesta. Contents of C15:0 iso, C18:11 trans-11 and C18:2 cis-9, trans-11 were increased (P < 0.05) in ruminal digesta by SO compared with control and HPO. In conclusion, supplementation of SO or HPO do not affect ruminal fermentation parameters, whereas HPO can increase load of ruminal P. bryantii. Also, results observed in our targeted bacteria may have depended on the saturation degree of dietary oils.